Hubungan kinerja otak dengan spiritualitas diukur dengan menggunakan Indonesia spiritual health assessment pada tokoh agama Kristen Gereja Mawar Sharon di Sulawesi Utara - Arie, Febryola; Pasiak, Taufiq F.; Kaseke, Martha M. (eBiomedik, 2016)
Abstract: To date, studies on brain field are growing and now they have touched the spiritual dimension. Amin divided the brain into five major systems, namely the prefrontal cortex, basal ganglia, the limbic system, gyrus cingulatus, and temporal lobes. One of the tools that can be used to measure the relationship between the performance of the brain and spirituality is Indonesia Spiritual Health Assessment (ISHA). There are four components of spirituality: spiritual experiences, positive emotion, meaning of life, and rituals. This sudy was aimed to determine the relationship between the performance of brain and the spirituality of religious leaders of Mawar Sharon Church in North Sulawesi. This was a descriptive analytical study with a survey method. Data were analyzed with Spearman correlation test. Subjects were 50 Christian religious leaders of Mawar Sharon Church in North Sulawesi. The results showed that there was a weak but significant correlation between gyrus cingulatus and spiritual experiences as well as positive emotions; and between the temporal lobe and meaning of life and ritual. Conclusion: There was a weak but significant correlation between the brain performance and the human spirituality measured by ISHA in religious leaders of Mawar Sharon Church in North Sulawesi.Keywords: brain, ISHA, spiritualityÂ Abstrak: Dewasa ini penelitian mengenai ilmu otak semakin berkembang bahkan hingga saat ini pendekatannya telah menyentuh dimensi spiritual. Amin membagi otak ke dalam lima sistem utama yaitu korteks prefrontalis, ganglia basalis, sistem limbik, girus singulatus, dan lobus temporalis. Salah satu alat yang dapat digunakan untuk mengukur hubungan antara kinerja otak dengan spiritualitas ialah instrumen Indonesia Spiritual Health Assessment (ISHA). Terdapat empat komponen spiritualitas yaitu pengalaman spiritual, emosi positif, makna hidup, dan ritual. Penelitian ini bertujuan untuk mengetahui hubungan antara kinerja otak dengan spiritualitas pada tokoh agama Gereja Mawar Sharon di Sulawesi Utara. Jenis penelitian ialah deskriptif analitik dengan metode survey. Data dianalisis menggunakan uji korelasi Spearman. Subjek penelitian ialah 50 orang tokoh agama Kristen Gereja Mawar Sharon di Sulawesi Utara. Hasil penelitian mendapatkan hubungan lemah namun bermakna antara girus singulatus dengan pengalaman spiritual dan emosi positif, dan lobus temporalis dengan makna hidup dan ritual. Simpulan: Terdapat hubungan yang lemah namun bermakna antara kinerja otak dengan spiritualitas manusia diukur menggunakan ISHA pada tokoh agama Kristen Gereja Mawar Sharon di Sulawesi Utara. Kata kunci: otak, ISHA, spiritualitas